2000
DOI: 10.1046/j.1460-9568.2000.00215.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal expression of noncatalytic TrkC NC2 isoform during early and late CNS neurogenesis: a comparative study with TrkC catalytic and p75NTR receptors

Abstract: The TrkC subfamily of primary high-affinity neurotrophin-3 receptors is composed of catalytic (kinase-containing; TrkC K) and noncatalytic (TrkC NC) isoforms generated by alternative splicing. We previously reported the presence of the mouse noncatalytic TrkC NC2 isoform in regions of neuronal differentiation [Menn, B., Timsit, S., Calothy, G. & Lamballe, F. (1998) J. Comp. Neurol., 401, 47-64]. In order to gain insight into specific roles for TrkC NC2 receptors during CNS neurogenesis, we compared its distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
12
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 45 publications
6
12
0
Order By: Relevance
“…Interestingly, these data are in agreement with a study reporting that TrkCNC2 was capable of inducing neuronal differentiation of avian neural crest cells in collaboration with p75 NTR (Hapner et al, 1998). Moreover, in mature neurons, TrkCNC2 distribution was specifically restricted to distinct areas of extending neurites, suggesting its involvement in synaptic plasticity and neuronal survival (Menn et al, 2000).…”
supporting
confidence: 92%
See 4 more Smart Citations
“…Interestingly, these data are in agreement with a study reporting that TrkCNC2 was capable of inducing neuronal differentiation of avian neural crest cells in collaboration with p75 NTR (Hapner et al, 1998). Moreover, in mature neurons, TrkCNC2 distribution was specifically restricted to distinct areas of extending neurites, suggesting its involvement in synaptic plasticity and neuronal survival (Menn et al, 2000).…”
supporting
confidence: 92%
“…In vivo studies showed that trkC NC2 transcripts were abundant in regions of neuronal maturation. In addition, TrkC NC2 expression in neural stem cells coincided with the exit of neural progenitors from the cell cycle, suggesting its involvement in neuronal and glial cell differentiation (Menn et al, 2000). Interestingly, these data are in agreement with a study reporting that TrkCNC2 was capable of inducing neuronal differentiation of avian neural crest cells in collaboration with p75 NTR (Hapner et al, 1998).…”
supporting
confidence: 90%
See 3 more Smart Citations